El Compromiso Ético en el Teatro Guineoecuatoriano: Pretérito Imperfecto y Los Hombres Domésticos de Tomás Ávila Laurel como modelos - Eman Khalifa (Beni-Suef University International Journal of Humanities and Social Sciences, 2022)
At the present time, African literature written in Spanish has reached an increase in the number of readers and researchers in different countries around the world. However, it remains understudied in the academic field of Spanish literary criticism. On the other hand, most of the studies carried out on this literature focus on prose, and very few studies analyze poetry or theater. For this reason, it is necessary to explore the status and characteristics of Equatoguinean theatre, represented by one of its most prominent figures, Juan Tomás Ávila Laurel. This article aims to study the ethical lines of the theater in Equatorial Guinea through two of Tomás Ávila's theatrical works: Imperfect Past (1991) and Domestic Men (1993). In his works, the author makes a just fictionalization of the daily reality of his country. Whatever the literary genre and the plot, his works are always charged with social criticism with a thread of irony.